Exploring the Views of Spanish Pre-Service Teachers on Phonics From a Quantitative Research Perspective - Fernández-Molina, Javier (Pedagogika, 2024)
English is especially demanding for Spanish speakers due to the greater number of sounds, the complex letter-sound relationship, and prosodic features. English phonics programmes may offer clearer, more comprehensive instruction. 84 pre-service teachers completed a questionnaire on the use of phonics in Spanish EFL preschool and primary classrooms. Results show that specific training is needed, not all participants favour this method, and a more eclectic approach to early literacy is advocated.